PREVALENCE OF INTESTINAL PARASITES ON MARKET SOLD FRUITS AND VEGETABLES - A.M, USMAN; E.A, BABEKER; ALIYU A.O, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Prevalence of intestinal parasites on fruits and vegetations sold in Bauchi North, Bauchi State, Nigeria was studiedfrom September to November, 2018. The study was to determine the prevalence and type of parasites on fruits and vegetables sold in the area. Four different fruits and vegetables were purchased from the main markets of the three selected Local Governments (Katagum, Jama’are and Shira) once in a week.A total of 288 samples, comprising of 144 fruits (watermelons, oranges, pineapples and Bananas) and 144 vegetables (cabbages, lettuces, onions and tomatoes) were purchased and examined for intestinal parasites using sedimentation method.Intestinal parasites were detected on 29(20.1%) fruits and 17(11.8%) vegetables.Entamoeba histolytica11(37.9%) and Ascaris lumbricoide7(41.2%)were the most prevalence parasites on the fruits and vegetables samples respectively.Poor environmental sanitation and preservation techniques by vendors, farmers and consumers were discovered to play a key role in contamination of the fruits and vegetables in the area. Contaminations of fruits and vegetables by intestinal parasites can be reduced or prevented through proper disposal of human and animal waste, washing of fruits and vegetables as well as educating vendors of food safety practice.